2017
DOI: 10.1590/0103-8478cr20160662
|View full text |Cite
|
Sign up to set email alerts
|

White grubs (Cyclocephala flavipennis) damaging perennial winter pastures in the South Region of Brazil

Abstract: White grubs (Cyclocephala flavipennis) damaging perennial winter pastures in the South Region of Brazil.Ciência Rural, v.47, n.5, 2017. In the South Region of Brazil, besides the traditional cultivation of winter-annual pastures, cultivation of winter perennial grasses, particularly tall fescue (Festuca arundinacea Schreb.) and orchardgrass (Dactylis glomerata L.), can be an alternative to reduce the periods of low forage production from native and cultivated perennial warm season grasses. Despite the growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The larvae of Cyclocephala use soil with organic matter as food, therefore being important for nutrient cycling such as C. paraguayensis Arrow, 1913). On the other hand, these larvae may consume plant roots, and some species can cause damage to crops such as C. forsteri which has been reported as potential pest to soybean crops ("soja", Glycine max (L.) Merr, Fabaceae) (Santos & Ávila 2007), or such as Cyclocephala flavipennis Arrow, 1914, which has been registered damaging pastures (Duchini et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The larvae of Cyclocephala use soil with organic matter as food, therefore being important for nutrient cycling such as C. paraguayensis Arrow, 1913). On the other hand, these larvae may consume plant roots, and some species can cause damage to crops such as C. forsteri which has been reported as potential pest to soybean crops ("soja", Glycine max (L.) Merr, Fabaceae) (Santos & Ávila 2007), or such as Cyclocephala flavipennis Arrow, 1914, which has been registered damaging pastures (Duchini et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In areas of natural pasture at the Brazilian Pampas, 28 species of Scarabaeidae were collected, distributed into the Dynastinae, Melolonthidae and Rutelinae (vAlmorbiDA et al 2018). DuChini et al (2017 identified four species of phytophagous Scarabaeidae in winter pastures of the Lages municipality, state of Santa Catarina.…”
Section: Resultsmentioning
confidence: 99%
“…Over this period, 10 harvests were performed; we labelled cycles 1–10. Cycles 2 and 8 were discarded because of insect attacks [ 39 ] and operational issues ( S2 Table ).…”
Section: Methodsmentioning
confidence: 99%